Matching of Individuals for Start-Ups: A Test of the O-Ring Theory - Bettina Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
In this paper I analyse how individuals match for for the purpose of setting up a new firm. As a theoretical basis I use the O-ring theory introduced by Kremer (1993) and applied to new firms by Fabel (2004). The O-ring theory predicts that individuals segregate between firms according to their level of ability. Further, the theory implies that a higher average ability level within firms is positively related to both the number of individuals and capital per head. Using a rich employer-employee data set on the whole population of Danish firms founded in 1998 most of the predictions of the O-ring theory are rejected. I find that individuals do not match with individuals with the same level of ability. Furthermore, ability and firm size turn out to be negatively correlated. There is only some support for the hypothesis concerning the positive relationship between ability and capital per head.
Keywords: M13; L26; D23; 330; Entrepreneurship; O-Ring Theory; Theory Test; Unternehmensgründung; Gruppenarbeit; Matching; Qualifikation; Einlage; Dänemark